2005
DOI: 10.1128/jb.187.1.396-399.2005
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Nitrogen from Nitrite and Trinitrotoluene in Pseudomonas putida JLR11

Abstract: Pseudomonas putida JLR11 releases nitrogen from the 2,4,6-trinitrotoluene (TNT) ring as nitrite or ammonium. These processes can occur simultaneously, as shown by the observation that a nasB mutant impaired in the reduction of nitrite to ammonium grew at a slower rate than the parental strain. Nitrogen from TNT is assimilated via the glutamine syntethase-glutamate synthase (GS-GOGAT) pathway, as evidenced by the inability of GOGAT mutants to use TNT. This pathway is also used to assimilate ammonium from reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…In E. coli, when there are high concentrations of ammonia, the enzyme glutamate dehydrogenase (GDH) catalyzes a reductive amination of 2-oxoglutarate to glutamate; when ammonium concentrations are low (Ͻ1 mM), a two-step reaction occurs involving the enzymes glutamine synthetase (GS) and glutamine:2-oxoglutarate aminotransferase (GOGAT) (16,17). In P. putida the latter pathway is used for the assimilation of nitrogen from reduced nitrate or nitrite and from trinitrotoluene (TNT) (7,45). It is therefore possible that the GS/ GOGAT pathway might be affected in the ⌬crp mutant, and/or that in the mutant the transport of inorganic nitrogen sources is compromised.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In E. coli, when there are high concentrations of ammonia, the enzyme glutamate dehydrogenase (GDH) catalyzes a reductive amination of 2-oxoglutarate to glutamate; when ammonium concentrations are low (Ͻ1 mM), a two-step reaction occurs involving the enzymes glutamine synthetase (GS) and glutamine:2-oxoglutarate aminotransferase (GOGAT) (16,17). In P. putida the latter pathway is used for the assimilation of nitrogen from reduced nitrate or nitrite and from trinitrotoluene (TNT) (7,45). It is therefore possible that the GS/ GOGAT pathway might be affected in the ⌬crp mutant, and/or that in the mutant the transport of inorganic nitrogen sources is compromised.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas spp. are also ubiquitous environmental colonizers, and Pseudomonas putida inoculates have been used to promote plant growth and in bioremediation (3,7,29,52,53,58). The key to the ubiquitous distribution of these bacteria is their use of highly sophisticated mechanisms to adapt to changes in the local environment.…”
mentioning
confidence: 99%
“…As a carbon source we used benzoate (15 mM), glucose (0.5% [wt/vol]), or sodium citrate (10 mM). When indicated M9 minimal medium without NH 4 Cl was used; this culture medium is referred as M8. When indicated L-lysine (10 mM), D-lysine (10 mM), ␦-aminovalerate (5 mM), glutarate (10 mM), or pipecolate (10 mM) was added to the culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Two Gram-positive isolates, strains TNT-8 and TNT-32, were able to use TNT as a nitrogen source, but the mechanism of nitrogen assimilation remains unclear (200). More recently, Ramos et al reported that Pseudomonas putida JLR11 (13)(14)(15) and Escherichia coli AB1157 (51) were able to use TNT as a nitrogen source for growth, reducing the nitro group and recovering the ammonium by the use of nitroreductases. The nitroreductases NfsA and NfsB, together with the N-ethylmaleimide reductase NemA, contributed to the ability of E. coli AB1157 to obtain usable nitrogen from TNT (51).…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%